2008
DOI: 10.1163/156856208783721001
|View full text |Cite
|
Sign up to set email alerts
|

Eluting characteristics of a platelet glycoprotein receptor antibody using a PLLA-coated stent

Abstract: Drug-eluting stents (DES) have emerged as a recognized alternative to treat stent restenosis but many questions remain regarding the optimal type and eluting characteristics of both drug and stent. The first component of the study examines the extent of surface coating of PLLA (poly(L-lactic acid)) on a Nitinol stent. The second characterizes the adsorption and elution rates of monoclonal mouse anti-human platelet glycoprotein (GP) IIIa antibody SZ-21 from a PLLA-coated surface. The PLLA coating was examined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The adsorption characteristics of the stents exposed to the mAb were tested by radioisotope technique with 125 I‐labelled SZ‐21. The elution rates were then measured in looped circuits at different velocities and durations 15. The mAb‐eluting stents were produced by immersing the PLLA‐coated stents in a 2.0 mg/mL solution of SZ‐21 antibody at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption characteristics of the stents exposed to the mAb were tested by radioisotope technique with 125 I‐labelled SZ‐21. The elution rates were then measured in looped circuits at different velocities and durations 15. The mAb‐eluting stents were produced by immersing the PLLA‐coated stents in a 2.0 mg/mL solution of SZ‐21 antibody at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The authors' previous studies have demonstrated that SZ‐21 could effectively inhibit platelet aggregation and the eluting characteristics of the platelet when eluted from L ‐polylactic acid (PLLA) polymer‐coated stents prepared by a special stent‐coating system in vitro 13–15. In this study, mAb is applied to the platelet glycoprotein IIIa receptor as the eluting drug of PLLA polymer‐coated stents, and passive absorption method is used to produce mAb‐eluting intravascular stents.…”
Section: Introductionmentioning
confidence: 99%
“…The elution rates were then measured in looped circuits at different velocities and durations. 15 The mAb-eluting stents were produced by immersing the PLLA-coated stents in a 2.0 mg/mL solution of SZ-21 antibody at 37 C. After passive absorption for 72 h, the quantity of SZ-21 absorbed on the stent wires was 0.8 mg/cm 2 . An in vitro perfusion circuit was designed to evaluate the release rates at different velocities (10 or 20 mL/min).…”
Section: Monoclonal Antibody-eluting Stentsmentioning
confidence: 99%
“…12 The authors' previous studies have demonstrated that SZ-21 could effectively inhibit platelet aggregation and the eluting characteristics of the platelet when eluted from L-polylactic acid (PLLA) polymer-coated stents prepared by a special stent-coating system in vitro. [13][14][15] In this study, mAb is applied to the platelet glycoprotein IIIa receptor as the eluting drug of PLLA polymer-coated stents, and passive absorption method is used to produce mAb-eluting intravascular stents. This study focuses on the inhibitory effect of this stent on stent thrombosis, neointimal hyperplasia, and in-stent restenosis by implanting mAb-eluting stents into iliac arteries of rabbits.…”
Section: Introductionmentioning
confidence: 99%